Legal Reform in Customary Marriage Law in Indonesia and South Africa for Inclusive Justice - Febrianty, Yenny; Ryendra, Nadya Restu; Ahmad, Asmida; Ariyanto, Ariyanto (Journal of Law and Legal Reform, 2025)
Customary law shapes South African and Indonesian culture and society. However, adopting customary marital law into national legal systems is difficult. These include value conflicts between regional traditions and positive law’s universal principles, such as recording marriages, protecting children, and ensuring gender equality. Within Indonesia’s legal system, customary law practices are not well accommodated. Customary law is acknowledged under South Africa’s constitution, however its application is fraught with difficulties. This study aims to (1) comprehend positive law and its correlation with customary marriage law, (2) analyze the difficulties of integrating customary marriage law with positive law in South Africa and Indonesia, and (3) evaluate the future prospects of this domain. The study’s findings and suggestions might foster a more equitable society and promote legislation that honors universal ideals and traditional customs. This comparative and qualitative study use normative legal techniques to analyze pertinent literature, legal concepts, and norms. This paper highlights the main barriers to merging positive and customary marriage legislation. Examples are administrative obstacles like marriage registration and customary norms that conflict with human rights. The proposed framework respects traditional values to uphold human rights and social fairness. Keywords include normative marriage law, positive law, social justice, gender equality, and legal integration.